Placenta Previa: Case Report - Farizan, Freza; Anwar, Junita Putri; Fani, Erliana (Jurnal Indonesia Sosial Sains, 2024)
Placenta previa is a significant obstetric complication that occurs during pregnancy, characterized by abnormal implantation of the placenta in the lower uterine segment. Risk factors for having had a previous caesarean section, multiple pregnancies, advanced maternal age, or having a history of uterine surgery at higher risk, a history of previous uterine curettage, may increase the likelihood of placenta previa. woman aged 29 years G3P2A0 38 weeks pregnant came with complaints of fresh blood coming out of the birth canal since 3 hours before entering the hospital about half of the pads. Previous history to an obstetrician with malpositioned ultrasound results and a history of 2 previous deliveries by cesarean section. Physical examination, blood pressure 110/70, pulse 78 times/minute, respiration 18 times/minute, temperature 360C, there was no clinical anemia, obstetric examination of the height of the uterine fundus (TFU) 33 cm with an estimated fetal weight (TBJ) 3100 gr, FHR 152 times/minute regularly, positive His 1-2 times/10 minutes 10-15 seconds each. From vaginal positive spots, no active bleeding, vaginal touch was not done. Ultrasound of the fetus in cephalic presentation, positive FHB, EFW 3100 gr, placenta corpus posterior closing OUI grade 3 SDP 6 cm PAI score 2 positive hypoechoic zone, negative lacuna, KTG category 1. From investigations, Hb was 10.2 gr/dl. Ht 30%, leukocytes 12,950 uL, platelets 322,000 uL, bleeding time and clotting time within normal limits. management carried out strict vital signs monitoring, planned sectio caesaria cito and given premedication injection of ceftriaxone 2gr and 250cc PRC blood supply. Placenta previa is a complex obstetric condition that requires careful diagnosis, monitoring and management. Prompt recognition of the condition, close monitoring of maternal and fetal safety, and timely intervention, such as cesarean section when indicated, are critical to reducing the risks associated with placenta previa.